2022
DOI: 10.14701/ahbps.22-043
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous resection of synchronous colorectal liver metastasis: Feasibility and development of a prediction model

Abstract: Backgrounds/Aims: Timing of resection for synchronous colorectal liver metastasis (CRLM) has been debated for decades. The aim of the present study was to assess the feasibility of simultaneous resection of CRLM in terms of major complications and develop a prediction model for safe resections. Methods: A retrospective single-center study of synchronous, resectable CRLM, operated between 2013 and 2021 was conducted. Upper limit of 95% confidence interval (CI) of major complications (≥ grade IIIA) was set at 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Reddy et al [ 13 ] reported that simultaneous colorectal resection and minor liver resection did not significantly increase the overall morbidity and mortality, and, conversely, simultaneous colorectal and major hepatic resections were associated with an increased risk of severe morbidity. Similarly, in a retrospective study [ 14 ] on 92 patients with synchronous resectable CLM, 27% of whom underwent major liver resection of ≥ 4 segments, the rate of major complications was 21.7%. The significant predictors of complications were medical comorbidities and major hepatectomy, which increased the complication rate to 40%.…”
Section: Discussionmentioning
confidence: 91%
“…Reddy et al [ 13 ] reported that simultaneous colorectal resection and minor liver resection did not significantly increase the overall morbidity and mortality, and, conversely, simultaneous colorectal and major hepatic resections were associated with an increased risk of severe morbidity. Similarly, in a retrospective study [ 14 ] on 92 patients with synchronous resectable CLM, 27% of whom underwent major liver resection of ≥ 4 segments, the rate of major complications was 21.7%. The significant predictors of complications were medical comorbidities and major hepatectomy, which increased the complication rate to 40%.…”
Section: Discussionmentioning
confidence: 91%
“…When it comes to choosing the optimal surgical strategy for resection of the primary tumor and synchronous liver metastases, the jury is still out. The data available ( Figure 1 ) are scarce to justify any one strategy over the other and are insufficient for use of open or minimally invasive surgery [ 12 , 14 , 15 , 16 , 17 ]. At present, there is only one prospective randomized trial (METASYNC) that has examined simultaneous and staged resection of CRC with synchronous liver metastases [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancers with liver metastases are common and associated with relatively favourable prognoses 1 . However, retroperitoneal lymph node metastases are less frequently observed and are correlated with poor outcomes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancers with liver metastases are common and associated with relatively favourable prognoses. 1 However, retroperitoneal lymph node metastases are less frequently observed and are correlated with poor outcomes. 2 Even though synchronous colorectal cancers and liver metastases are operated upon simultaneously and by minimally invasive approaches, retroperitoneal lymph node dissections are still a regular indication for open operations.…”
Section: Introductionmentioning
confidence: 99%